A test of interaction effects between alcohol protective behavioral strategies and antecedents of alcohol-related consequences. (March 2021) - Schwebel, Frank J.; Richards, Dylan K.; Pearson, Matthew R.; ,
Highlights: Protective behavioral strategies (PBS) associated with reduced alcohol harms. Near 70% of interactions of potential risk factors and PBS were significant. Interaction effects were largely buffering effects. PBS use generally decreases risk of a wide variety of risk factors. Replication and RCTs are needed to better understand the moderating effect of PBS. Abstract: The purpose of the present study was to examine interaction effects between alcohol protective behavioral strategies (PBS) and a variety of risk and protective factors for experiencing negative alcohol-related consequences using data from a large, multi-site sample of college students. We recruited 5090 college students (71.2% female; 77.4% White; Mean Age = 20.89, SD = 4.44) who reported any alcohol use in the past month from psychology department participant pools at 10 universities across the U.S. to complete an online survey. Alcohol PBS use was a statistically significant negative predictor of alcohol-related problems while controlling for each antecedent variable individually. In terms of moderation effects, 26 out of 35 interactions (74.3%) were statistically significant in the models controlling only for sex. When controlling for frequency and quantity of alcohol use, 24 of 33 interactions (72.7%) were statistically significant. The nature of these interaction effects was largely the same: more frequent alcohol PBS use reduced the positive associations between risk factors and alcohol-related problems. The lack of specificity of these interaction effects calls into question the limited contributions of tests of interaction effects between alcohol PBS and individual antecedent variables. Comprehensive tests of interaction effects between alcohol PBS and antecedent variables with large samples are needed to move the field forward, especially replication attempts of interactions effects reported in single studies.